2000
DOI: 10.1006/viro.2000.0675
|View full text |Cite
|
Sign up to set email alerts
|

Role of M Protein Aggregation in Defective Assembly of Temperature-Sensitive M Protein Mutants of Vesicular Stomatitis Virus

Abstract: The goal of these experiments was to determine the steps in virus assembly that are defective at the nonpermissive temperature in temperature-sensitive (ts) matrix (M) protein mutants of vesicular stomatitis virus. It has been proposed that mutations in M protein either reduce the binding affinity for nucleocapsids or lead to aggregation, reducing the amount of M protein available for virus assembly. Cytosolic or membrane-derived M proteins from wild-type VSV and two ts M protein mutant viruses, tsM301 and tsO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The ability of radiolabeled wt or mutant M protein to exchange with unlabeled M protein in virion NCM complexes was assayed as described previously (7). Briefly, in vitro transcription and translation (Promega TNT) was used to produce […”
Section: Mutagenesis and Bacterial Expression Of M Proteinmentioning
confidence: 99%
“…The ability of radiolabeled wt or mutant M protein to exchange with unlabeled M protein in virion NCM complexes was assayed as described previously (7). Briefly, in vitro transcription and translation (Promega TNT) was used to produce […”
Section: Mutagenesis and Bacterial Expression Of M Proteinmentioning
confidence: 99%
“…Considered the key protein for assembly and budding, M is found mainly in the cytoplasm (80%) and sometimes is linked to the plasma membrane (10 to 20%) (51). The M protein can also be found in the nucleus (31), where it can inhibit transcription by interacting with the RNA polymerase II TFIID complex (1,6,(13)(14) and with NUP98, resulting in an inhibition of the nucleocytoplasmic transport of host mRNAs (20,34). It also inhibits cellular translation (15) by modifying the initiation complex eIF4F through dephosphorylation of the initiation factors eIF4E and 4E-BP1 (10).…”
mentioning
confidence: 99%
“…L111 in the VSV Ind M protein is located at the alpha-helix region in which the amino acid is surrounded by hydrophobic amino acids (47). It has been suggested that the L111F mutation in the M protein of VSV Ind aggregates M protein on the cytoplasmic membrane and prevents the initiation of nucleocapsid-M protein complex formation (28) for the assembly of VSV particles at a nonpermissive temperature (39°C). Leucine is not present exactly at the same 111th position in the M protein of VSV NJ , but it is found at the 110th position.…”
Section: Discussionmentioning
confidence: 99%
“…One of the temperature-sensitive M gene mutants of the VSV Ind Orsay strain, the tsO23 mutant, has shown limited replication in a mouse glial cell line at 37°C and 39°C (27). It has been demonstrated that the temperature sensitivity of the tsO23 mutant was the result of improper assembly or lack of initiation in viral assembly, with the characteristic bullet-shaped structure at 39°C (28,29). In addition, the original tsO23 mutant lost its neurovirulence in mice, as demonstrated by direct inoculation of the virus into the brain (27).…”
Section: Esicular Stomatitis Virus (Vsv) Is a Rapidly Replicating Vmentioning
confidence: 99%